Strategi Pembelajaran Akidah Akhlak dalam Pembentukan Akhlak Mulia Siswa Kelas V MSU Nashrus Sunnah Madiun - Amatullah Taqiya Zahra; Anisa Rosida Kurnia P; Talita Vingki Edi Kustanti; Gracea Rimadanti Tanzaen; Ayu Tegar; Faridatul Munawaroh (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
Moral education at the elementary level has become increasingly urgent as children are exposed to rapid digital transformation and inconsistent moral supervision across home and school contexts. This study aims to analyze how Aqidah Akhlak learning strategies contribute to the formation of noble character among fifth-grade students at Madrasah Salafiyah Ula Nashrus Sunnah Madiun. A qualitative descriptive case-study design was employed to obtain an in-depth understanding of instructional practices, religious habituation, and supporting and inhibiting factors in character formation. Data were collected through semi-structured interviews with the headmaster, an Aqidah Akhlak teacher, and student representatives, non-participant observations of daily religious activities, and documentation of school programs and learning materials. The data were analyzed through data condensation, data display, and conclusion drawing, supported by source and technique triangulation. The findings indicate that Aqidah Akhlak learning operates through three integrated mechanisms: teacher modeling, structured religious habituation, and positive reinforcement. Morning dhikr, congregational Dhuha prayer, the jimpitan charity program, congregational prayer routines, storytelling, advice, reward, and educative sanctions collectively internalize honesty, discipline, patience, simplicity, responsibility, and compassion. The novelty of this study lies in identifying the madrasah-based character formation ecosystem as a continuous interaction among classroom instruction, daily worship habituation, teacher role modeling, and parent-school synergy. The study implies that noble character formation requires not only curriculum delivery but also a consistent educational ecology across school, family, and digital environments.